THE TRANSFORMATION OF WOMEN'S SPIRITUALITY IN URBAN SUFISM: A PHENOMENOLOGICAL STUDY OF THE MAJLIS DZIKIR GURU SEKUMPUL - Lina Munadlirotul Qomariyah (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
Urban Sufism emerged as a response to the spiritual crisis and moral degradation of modern society, particularly among urban women. Modernity and urbanization have created a void of meaning and weakened people's spiritual connection with God. In this context, the Sufi teachings of KH. Zaini Abdul Ghani (Guru Sekumpul) offer spiritual transformation based on Islamic moral values and spirituality. This study aims to analyze the role of Guru Sekumpul's Sufism in building spiritual intelligence and strengthening the religiosity of women in the majlis environment, while also reviewing its relevance to the challenges of urban life. This study uses a qualitative approach with a library research method enriched with observations and light interviews with female congregants of the Majlis Thariqah Guru Sekumpul in urban areas. The results show that Sufi practices in the Guru Sekumpul Majlis, such as zikr, recitation, and social activities, shape the character of insan kamil and strengthen the social solidarity of urban women. In addition, the emergence of a community of social volunteers is a manifestation of spiritual intelligence that balances worldly and spiritual life. This study contributes to the development of modern Sufism studies and offers a new perspective on women's spirituality in the context of urban society.